RESPON PERTUMBUHAN STEK BATANG TANAMAN BUAH NAGA MERAH (Hylocereus costaricensis) TERHADAP KONSENTRASI DAN LAMA PERENDAMAN AIR KELAPA MUDA - Azis Febrianto; Hermansyah Hermansyah; Faiz Barchia (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2019)
[GROWTH OF DRAGON FRUIT (Hylocereus constaricensis) STEM CUTTINGS AS AFFECTED BY CONCENTRATIONS AND DIPPING TIMES OF COCONUT WATER]. Dragon fruits (Hylocereus constaricensis) is commonly propagated vegetatively by using stem cutting. In this respect the use of natural plant growth regulator, such as coconut water, to promote the growth of the cuttings is very important. The objectives of this experiment were to evaluate water coconut concentration, dipping time of stem cutting in the coconut water, and the combination of both to promote the growth of dragon fruit cuttings. The experiment was arranged in Randomized Complete Block Design (2 factors, 5 replications). The first factor was the concentration of coconut water, consisting of 5 levels: 20, 40, 60, 80, and 100%. The second factor was dipping time of cutting in the coconut water, consisting of 4 levels: 2, 4, 6, and 8 minutes. The results showed that the increasing coconut water concentration had increased the shoot growth in a liner fashion. A similar trend was also observed for coconut water dipping time. The highest shoot growth was found on 60 % coconut water.